Nature Unbound: A Study of Jayanta Mahapatara’s Selected Poems: Exploring the Poetry of Jayanta Mahapatra (Journal of Advances and Scholarly Researches in Allied Education, 2019)
One of the most widely known and published Indian English poets of our time is Jayanta Mahapatra. Like A.K. Ramanujan, he is widely read and discussed both at home and abroad. But unlike Ramanujan, Mahapatra is difficult to read for obscurity, complexity and allusiveness in his poetry. But his contrived image, learned vocabulary set him a class apart from most of his contemporaries. At the same time, in his desire to acclimatize an indigenous tradition to English language and create something new in Indian English, he shares some of the concerns of the well-known Indian English poets of our time. Like Nissim Ezekiel, Kamala Das, Keki N. Daruwalla, Shiv K. Kumar and A.K. Ramanujan, Jayanta Mahapatra has given Indian poetry in English a local habitation and a larger public outside India. Jayanta Mahapatra published his poetry in the United States of America.